Analisis Pemeliharaan Preventif Gardu Kubikal untuk Meningkatkan Keandalan Sistem Distribusi Listrik di PT. Haleyora Powerindo - Farid Wiherdiansyah; Didik Aribowo (Fakultas Teknik UMRI, 2024)
This research discusses the importance of preventive maintenance of cubicle substations to improve the reliability of the electricity distribution system at PT Haleyora Powerindo. Cubicle substations, as important components in the distribution network, require special attention to prevent unexpected damage and maintain continuity of electricity supply. This research uses literature study, observation, and interview methods with a focus on the stages of maintenance, such as preparation, implementation, and completion, as well as identification of potential causes of damage such as corona, animals, and moisture. With the proper implementation of maintenance, system reliability can be maintained, reducing the risk of disruption, and improving the quality of service to consumers.